1966
DOI: 10.1111/j.1476-5381.1966.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pronethalol on the Cardiovascular Actions of Catecholamines During Blockade by Phenoxybenzamine

Abstract: This paper presents the results of experiments in which some cardiovascular parameters of the anaesthetized dog were recorded, in an attempt to elucidate the mechanisms involved. METHODSSeventeen mongrel dogs of either sex weighing between 8 and 18.5 kg were anaesthetized with pentobarbitone sodium (30 mg/kg, intravenously) and both vagi were cut in the neck. Blood pressure was measured with a Statham transducer (model P23AA) and a carrier preamplifier from a cannula in the left carotid artery. During artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Eltherington & Horita (1960) observed that after blockade of the vascular areceptors by phenoxybenzamine, injection of the 8-receptorblocking agent dichloroisoprenaline (DCI) caused a return of the adrenaline pressor response to approximately 50% of the control value. Moreira & Osswald (1965), Gulati, Gokhale & Udwadia (1965), Tuttle (1965) and Garrett, Malafaya-Baptista & Osswald (1966) confirmed this observation on the blood pressure and demonstrated that this action of DCI extended to the nictitating menmbrane and to the femoral blood flow; it was also observed with other s-receptor blocking agents. Although tentative explanations have been suggested, the meclhanism of this phenomenon remains controversial, in view of the complexity of the cardiovascular parameters.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Eltherington & Horita (1960) observed that after blockade of the vascular areceptors by phenoxybenzamine, injection of the 8-receptorblocking agent dichloroisoprenaline (DCI) caused a return of the adrenaline pressor response to approximately 50% of the control value. Moreira & Osswald (1965), Gulati, Gokhale & Udwadia (1965), Tuttle (1965) and Garrett, Malafaya-Baptista & Osswald (1966) confirmed this observation on the blood pressure and demonstrated that this action of DCI extended to the nictitating menmbrane and to the femoral blood flow; it was also observed with other s-receptor blocking agents. Although tentative explanations have been suggested, the meclhanism of this phenomenon remains controversial, in view of the complexity of the cardiovascular parameters.…”
mentioning
confidence: 75%
“…Since the reversal was obtained only with concentrations of di'benamine which cause a parallel shift of the dose-effect curves to the right and was not observed in the presence of higher concentrations of dilbenamine, which produce unsurmountable antagonism, one could speculate, as Garrett et al (1966) have done, that " spare receptors" are involved in the reversal phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the results with antagonistic action between the alpha and beta-blocking agents, Olivares et al suggested that beta-blocking agents "un blocked" the alpha-receptor which had been previously blocked by the alpha-blocking agent (15). On the other hand, it has been suggested that in tissues with alpha and beta receptors, the beta-blockade subsequent to alpha-blockade results in unmasking of re sidual alpha-adrenergic activity of the agonists with mixed activity, not previously blocked by the alpha-blocking agent (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%